2000
DOI: 10.1067/mtc.2000.109516
|View full text |Cite
|
Sign up to set email alerts
|

Results of a total aortic arch replacement for an acute aortic arch dissection

Abstract: Resecting both the ascending and transverse aorta, irrespective of whether the intimal tear is located in the aortic arch, may be an acceptable alternative at experienced centers because of its low mortality and good midterm results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…On the other hand, some studies have reported on the use of an initial, extensive approach for the surgical treatment of AAD, such as total arch replacement or root replacement, to prevent future reoperations 9‐11 . Because few studies have reported on the outcomes of late reoperations after acute type A aortic aneurysm, 7‐12 the real overall long‐term outcome of AAD remains unknown. The results of this study showed that late reoperations could be performed safely, even when extended reoperative procedures were required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some studies have reported on the use of an initial, extensive approach for the surgical treatment of AAD, such as total arch replacement or root replacement, to prevent future reoperations 9‐11 . Because few studies have reported on the outcomes of late reoperations after acute type A aortic aneurysm, 7‐12 the real overall long‐term outcome of AAD remains unknown. The results of this study showed that late reoperations could be performed safely, even when extended reoperative procedures were required.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of surgical intervention for AAD have improved, survivors remain at risk of further surgical interventions due to persistent, dissected residual aorta 6‐8 . Several reports have suggested that extended procedures can prevent future reoperations, 9 although the mortality in such high‐risk cases remains high 9‐11 . To compare the relative advantages of less invasive and extended initial approaches, it is necessary to assess the results of surgical reinterventions after initial repair of AAD.…”
mentioning
confidence: 99%
“…To improve late surgical outcome, total aortic replacement is recommended as the initial surgical approach for acute type A dissection, by us and others. [1][2][3][4] Several surgical approaches, such as the separate graft, 5,6 en bloc, 5 hybrid, 7 and branched stent graft placement 8 techniques have been adopted for aortic arch reconstruction. We reviewed our experience of surgery for acute type A dissection using total arch replacement, combined with stented elephant trunk implantation, with preservation of the autologous brachiocephalic vessels.…”
Section: See Editorial Commentary Page 106mentioning
confidence: 99%
“…These include a conservative strategy with a simple replacement of the ascending aorta and hemiarch to a more aggressive one with a total aortic replacement. To improve late surgical outcomes, extended aortic replacement has been recommended for initial surgical treatment of acute type A dissection, and is not associated with higher morbidity and mortality [ 7 ],[ 10 ].…”
Section: Discussionmentioning
confidence: 99%